2015
DOI: 10.1186/s13063-015-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining curcumin (C3-complex, Sabinsa) with standard care FOLFOX chemotherapy in patients with inoperable colorectal cancer (CUFOX): study protocol for a randomised control trial

Abstract: BackgroundThe need for low toxicity adjuncts to standard care chemotherapy in inoperable colorectal cancer, with potential to improve outcomes and decrease the side-effect burden, is well recognised. Addition of the low toxicity diet-derived agent, curcumin (the active ingredient of turmeric), to standard oxaliplatin-based therapy has shown promise in numerous pre-clinical studies.Methods/DesignThis study is the first to combine daily oral curcumin with standard care FOLFOX-based (5-fluorouracil, folinic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Phase I clinical trials have shown safety, tolerability, and nontoxicity of curcumin even at high doses (8 g/day) but exhibited poor bioavailability in humans (Sharma et al, 2004;Kanai et al, 2013). Despite bioavailability challenges, clinical trials with curcumin either alone or in combination as an anticancer agent have shown efficacy against several disease sites such as breast (Bayet-Robert et al, 2010), prostate (Mahammedi et al, 2016), pancreatic (Epelbaum et al, 2010;Kanai et al, 2013), colorectal (Sharma et al, 2004;Carroll et al, 2011;Irving et al, 2015;James et al, 2015), and hematological malignancies (Ghalaut et al, 2012). Latest information on various preclinical and clinical anticancer trials using curcumin is reviewed in Doello et al (2018).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…Phase I clinical trials have shown safety, tolerability, and nontoxicity of curcumin even at high doses (8 g/day) but exhibited poor bioavailability in humans (Sharma et al, 2004;Kanai et al, 2013). Despite bioavailability challenges, clinical trials with curcumin either alone or in combination as an anticancer agent have shown efficacy against several disease sites such as breast (Bayet-Robert et al, 2010), prostate (Mahammedi et al, 2016), pancreatic (Epelbaum et al, 2010;Kanai et al, 2013), colorectal (Sharma et al, 2004;Carroll et al, 2011;Irving et al, 2015;James et al, 2015), and hematological malignancies (Ghalaut et al, 2012). Latest information on various preclinical and clinical anticancer trials using curcumin is reviewed in Doello et al (2018).…”
Section: Phytochemicals Evaluated In Clinical Trialsmentioning
confidence: 99%
“…A preliminary study from our lab showed that DMC is an effective antitumor agent that downregulates survivin and upregulates E‐cadherin in colon cancer cells . Moreover, recent studies reported that curcumin combined with FOLFOX chemotherapy was clinically safe and tolerable and capable of preventing colon cancer growth . Therefore, combining DMC with chemotherapy should have potent antitumor effects in colon cancer cells.…”
Section: Introductionmentioning
confidence: 96%
“…Curcumin (1,7-Bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione) is a polyphenolic compound isolated from Curcuma longa , that has demonstrated a wide range of biological activities; anti-inflammatory, 1014 anti-oxidative, 1519 antibacterial, 2026 rheumatoid arthritis, 2730,12,31–33 Alzheimer’s, 3442 psoriasis, 43,44 and diabetes. 4553 Curcumin has been investigated for its anti-cancer properties for cancers such as lung, 5458 ovarian, 5965 colorectal, 6673 and pancreatic. 7481 …”
Section: Introductionmentioning
confidence: 99%